Determinasi Pengetahuan, Kompetensi, Dan Pelatihan Terhadap Konsistensi Kader Posyandu Dengan Efektivitas Kerja Sebagai Variabel Intervening Di Posyandu Kabupaten Bintan - Adma Gumilang, Mardian; Wibisono, Chablullah; Wayan Catrayasa, I (Program Studi Manajemen FEBM UMRAH, 2024)
Posyandu is a health care institution carried out from, by and for the community guided by related officers. The cadres have not been effective in working, this can be seen from the decreasing interest of the community to bring their children to the posyandu, this is due to the lack of health efforts in terms of promotive functions and roles of the posyandu then the role of cadres that has not been optimal. The purpose of this study was to determine the determination of knowledge on the consistency of cadres through the effectiveness of posyandu work at the Posyandu Bintan Regency. To determine the determination of competence on the consistency of cadres through the effectiveness of posyandu work at the Posyandu Bintan Regency. To determine the determination of training on the consistency of cadres through the effectiveness of posyandu work at the Posyandu Bintan Regency. To determine the determination of work effectiveness on the consistency of posyandu cadres at the Posyandu Bintan Regency. This study was used for explanatory purposes (explanatory or confirmatory), namely explaining the causal relationship between variables through hypothesis testing. This study is correlational, namely research that attempts to see between two or more variables that have a relationship and how the direction of the relationship is. The results of the study are that competence through work effectiveness has a significant influence on cadre consistency through the results of the path coefficient. Based on the results of the study, it was concluded that when competence increases with the intervening of work effectiveness, it has an effect on the consistency of Posyandu cadres in Bintan Regency. Training through work effectiveness has a significant effect on the consistency of cadres through the results of the path coefficient. Based on the results of the study, it was concluded that when training increases with the intervening of work effectiveness, it has an effect on the consistency of Posyandu cadres in Bintan Regency. Work effectiveness has a significant effect on consistency. Based on the results of the study, it was concluded that when work effectiveness increases, it will increase the consistency of Posyandu cadres in Bintan Regency.